Bullying, vitimização e agressividade juvenil: um estudo de caso - SILVA, Felipe Ribeiro (Universidade Federal do Pará, 2014)
This work present some discussions about aggressively youth, bullying e victimization theme in school of international and national context. It´s present a field research of the type selfreport about the theme in a public school of Belém-PA- Brazil. The work sought to evaluate the students’ view on the family care and if they suffer from domestic violence. We also raised the acts of violence and suffering, whether or not to carry weapons to school, beyond the perception of young people regarding their neighborhood residents an their possible reactions in situations of conflict or violence. The fieldwork was conducted between august to November 2010. It may be noted in the study results that bullying (although cases reduced) is present in virtually all series and the aggressiveness of youth is manifested in many ways found.